(untitled) (World Bulletin of Education and Learning, 2026)
This article covers the issues of developing the creative activity of technology teachers in a digital environment from scientific-theoretical and practical perspectives. The content of the concept of creative activity, its role in pedagogical activity, and the possibilities for development in a digital educational environment are analyzed. Methodological recommendations aimed at increasing the creative potential of teachers based on innovative approaches, interactive methods, and digital tools will also be developed.